Headache across the spectrum of kidney disease: epidemiology, clinical patterns, pathophysiological mechanisms, and management-a narrative review - Amin Roshdy Soliman; Rabab Mahmoud Ahmed; Ahmed Fayed (The Egyptian Journal of Internal Medicine, 2026)
Abstract Headache is a frequent yet incompletely characterized symptom across kidney-disease populations. Most available literature focuses on chronic kidney disease (CKD), hemodialysis, and kidney transplantation, whereas several clinically important kidney disorders remain poorly studied. This narrative review integrates evidence across the kidney-disease spectrum to summarize headache epidemiology, clinical patterns, potential mechanisms, and management, while explicitly identifying major evidence gaps. A structured literature search was conducted in PubMed/MEDLINE, EMBASE, and the Cochrane Library from database inception through 31 JULY 2025 for studies addressing headache epidemiology, phenotype, mechanisms, risk factors, or management in patients with kidney disease. Additional eligible publications were identified through reference-list screening. Reported headache prevalence varies substantially across kidney-disease settings. The highest burden is described in patients receiving hemodialysis, with dialysis-related headache estimates ranging from 27% to 73% in adults and exceeding 75% in some pediatric cohorts. One single-centre comparative study suggests that dialysis-related headache may occur less frequently with online hemodiafiltration than with conventional hemodialysis. Headache prevalence appears lower in nondialysis CKD than in hemodialysis populations and is generally lowest following kidney transplantation. Evidence remains limited or absent in AKI, peritoneal dialysis, glomerular diseases, renal artery stenosis, and tubulointerstitial disorders. Migraine is among the most commonly reported headache phenotypes across several kidney-disease populations. Proposed mechanisms are heterogeneous and likely multifactorial, involving rapid osmotic and metabolic shifts, vascular dysregulation, inflammatory pathways, electrolyte abnormalities, medication effects, and other treatment-related factors. Management should therefore combine exclusion of secondary causes, correction of reversible kidney-related contributors, optimization of dialysis parameters when applicable, and carefully selected non-pharmacologic and pharmacologic therapies. Headache remains under-recognized in kidney disease. Future research should use standardized headache definitions and prospective kidney-specific designs to clarify prevalence, mechanisms, clinical impact, and treatment safety across understudied populations.